Down-Regulation of CYP79A1 Gene Through Antisense Approach Reduced the Cyanogenic Glycoside Dhurrin in [Sorghum bicolor (L.) Moench] to Improve Fodder Quality - Pandey, Arun K.; Madhu, Pusuluri; Bhat, Basrur Venkatesh (Frontiers in Nutrition, 2019)
A major limitation for the utilization of sorghum forage is the production of the cyanogenic glycoside dhurrin in its leaves and stem that may cause death of cattle feeding on it at the pre-flowering stage. Therefore, we attempted to develop transgenic sorghum plants with reduced levels of hydrogen cyanide (HCN) by anti-sense mediated down-regulation of the expression of cytochrome P450 CYP79A1, the key enzyme of dhurrin biosynthesis pathway. CYP79A1 cDNA was isolated and cloned in antisense orientation, driven by rice Act1 promoter. Shoot meristem explants of sorghum cultivar CSV 15 were transformed by particle bombardment method and 27 transgenics showing the integration of transgene were developed. The biochemical assay for HCN in the transgenic sorghum plants confirmed significantly reduced HCN levels in transgenic plants and their progenies. The HCN content in the transgenics varied from 5.1 to 149.8 µg/g compared to 192.08 µg/g in the non-transformed control on dry weight basis. Progenies with reduced HCN content were advanced after each generation till T3. In T3 generation, progenies of two promising events were tested which produced highly reduced levels of HCN (mean of 62.9 and 76.2 µg/g, against the control mean of 221.4µg/g). The reduction in the HCN levels of transgenics confirmed the usefulness of this approach for reducing HCN levels in forage sorghum plants. The study effectively demonstrated that the antisense CYP79A1 gene deployment was effective in producing sorghum plants with lower HCN content which are safer for cattle to feed on.